Digital Financial Reports for Female Shrimp Paste Entrepreneurs for Sustainable Competitive Financial Advantage - Iwan Kusmayadi; Djoko Suprayetno; Laila Wardani; Muhammad Mujahid Dakwah; Muhammad Ahyar; Siti Sofiyah (Unram Journal of Community Service, 2025)
Jor Hamlet, Jerowaru Village, Jerowaru District, East Lombok Regency, is a center for shrimp paste production with significant development potential. Limited access to capital is the main constraint due to the low awareness and financial literacy among most entrepreneurs. This situation requires intervention through education, carried out with direct assistance in the form of workshops on the introduction and use of digital financial reporting applications. This training aims to enhance financial management skills in a more practical and professional manner, thereby improving business competitiveness and sustainability. The focus of this mentoring activity is the introduction of the application and practical simulation of automatically preparing financial reports using the BukuWarung application. The structured and effective mentoring method is carried out in three main stages: First, initial analysis and preparation, which involves identifying the partner's needs and preparing materials and manuals. Second, workshops, which involve introducing and directly simulating the use of the BukuWarung application. This includes guidance on downloading the app, introduction to its main features and functions, account creation, recording transactions, evaluating financial reports to measure business performance, as well as interactive discussions. Third, monitoring and evaluation, by ensuring that participants can use the application independently and consistently. This mentoring activity has had a positive impact on entrepreneurs, including improved financial literacy and strengthened commitment to regularly record business activities in financial reports. This practice allows them to enhance the efficiency and competitiveness of their businesses.